종합병원 외래환자 투약대기시간 단축에 관한 연구 : 약국의 자동정제포장기 도입에 대하여 - 유효열 (연세대학교 보건대학원, 1991)
[한글] 한 종합병원에서 환자에 대한 서비스를 강화하는 것은 병원의 경쟁력 향상을 가져오므로 수익증대에 기여하게 된다. 환자에 대한 서비스중 외래환자의 대기시간 단축에 대한 과제는 국내종합병원의 공통적인 과제로써 대기시간중 특히 투약대기시간에 대하여는 특별한 대안이 없는 실정이다. 이 연구에서는 외래환자 투약대기시간을 단축하기 위한 대안으로 일본에서 개발되어 현재 효율적으로 사용되고 있는 컴퓨터를 이용한 자동정제포장기기를 국내 종합병원에 적용시 그에 대한 적합성 및 효과에 대한 타당성 분석을 시도하였으며 투자범위를 결정하기 위하여 자동정제포 장기기의 수량을 조정하여 실험하였으며, 투자에 대한 비용편익분석을 하였다. 효과분석을 하기위한 컴퓨터프로그램을 개발하여 실험하였으며 그 결과는 다음과 같다. 대안1 : 기기 1대를 사용할 경우에는 기기가 조제업무량을 감당하기가 어려워 오히려 현재보다 대기시간이 증가하였으므로 대안으로는 부적합하다. 대안2 : 기기 2대를 사용할 경우에는 환자의 대기시간이 현저히 단축되어 전환자가 15분 이내로 단축되었으므로 현실성이 있다고 판정되어 비용편익분석 결과 5년간의 순편익이 4억3천만원이 발생되어 매우 효과적이라고 평가된다. 대안3 : 기기 3대를 사용할 경우에는 환자의 대기시간은 대안 2와 같은 결과이었으며 기기의 추가 투자로 인하여 대안2보다 편익이 감소하였다. 본 자동화시스템은 현싯점에서 약국의 조제업무를 최고로 자동화로 추진한 기기로써 기술적인면이나 운영상에도 특별한 문제점이 없다. 이러한 시스템의 사용으로 인하여 약국의 약사인력에 대한 조정효과보다는 환자에 대한 투약서비스(진료실, 투약창구등)를 위하여 약사의 직무의 변화가 예상된다. 본 연구는 확률적 시뮬레이션모델에 의한 분석방법이 아니므로 일반화하기에는 제한점이 있다. 향후 입원환자의 투약서비스를 위한 본 기기에 대한 연구가 계속되어야 하며 병원의 정보시스템(컴퓨터시스템)과 연관하여 그에 대한 가치분석도 연구되어야 할 과제이다. 또한, 추후 이러한 시스템을 도입하여 실제로 사용한 효과에 대한 평가 연구도 진행되어야 할 것이다. [영문] It is widely accepted that improvement in patient care and services may contribute to increase profit in general hospital through increasing net income and efficient management. Among those services for in- and outpatients, the waiting time for outpatients has been a major concern for all solutions so far. To improve drug dispensing time, automatic tablet counting & packing system (ATC) has widely used in Japan and it proved to be very effective method to solve that problem. This study analyzed the effectiveness of ATC system in Korea, and the total number of ATC systems required to improve the waiting time as well as cost and benefit. Computer simulation model was developed for this study and the results were as follows : 1. 1 ATC system : It increased the waiting time because the total number of drug dispenses exceeded a capability of one system. 2. 2 ATC system : The waiting time for drug dispense was dramatically reduced by 15 minutes. And also, cost and benefit analysis showed that it increased profit of ￦ 430,000,000 for 5 year. 3. 3 ATC system : The waiting time did not show any significant improvement compared to 2 ATC system. At present time, ATC system, which is automatic drug dispensing system, doesn't cause any technical problems so far. ATC system may play a major role to improve drug dispensing time and it may change pharmacist's responsibilities in general hospital, such as better personal services for all patients instead of dispensing medicines. And, administrators should emphasize better patient care to pharmacist rather than reducing man power through ATC system. There may be a limit for general use in hospital, because this study did not analyze the effectiveness of ATC system in practice, not by simulation. Also, further study is necessary to employ ATC system for inpatients as well as in conjunction with the total hospital information system.
병원행정학과/석사